REPRESENTASI PRIMORDIALISME DALAM FILM DOKUMENTER MAMA AMAMAPARE - Immanuel, Janriver; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Film as one of mass media that the many people use. Function of film is consolation for people, to confer an information, and to confer knowledge. Film has divided became 3, there is, fiction film, documentary film, and docudrama. As one of film in Documentary film of Mama Amamapare to evidence exitence of baby shaman in Mimika Papua. from film, writer want to see Primordialism that happen with people about baby shaman.Design of this research qulitative design with analysis unit semiotika of Ferdinan de Saussure. In this research use analysis unit data resort to scene in film of Mama Amamapare to evidence Primordialism. To prove reflection Primordialism in film of Mama Amamapare this research use contents analysis method which one analysis unit use by the scene be shared two classification, there is audio and visual to prove aspect primodialism. Result of this resarch is, sign has taken by means of scene to certain to gotten Primordialism in film of Mama Amamapare. Signifier be able in this research to result have enough to prove in direct of Primordialism to found in film of Mama Amamapare. Signified be able in this film to explicit according to knotted from signifier on the top. Is true, people in Amamapare entrust of pregnancy and birth with baby shaman. Keyword : representation, primordialism, semiotic